Translation Errors Across Genres: A Research Perspective - Cozma Mihaela (Romanian Journal of English Studies, 2019)
Even if there may be types of translation errors which have a rather general character, in most of the cases they are closely related to the genre that the text to be translated represents. The paper offers an analysis of the translation errors contained by the assignments of 30 MA students in Translation Studies from the West University of Timisoara, Romania. The assignments consist in the translation from English into Romanian of texts belonging to three different genres: travel guides, legislation, and medical case reports. The errors are analyzed both quantitatively and qualitatively, with a view to arriving at conclusions of relevance for the improvement of the training process.